Giant linear strain gradient with extremely low elastic energy in a perovskite nanostructure array - Y. L. Tang (Nature Portfolio, 2017)
Inherent elastic strains are useful to tune the physical properties of functional materials but it is difficult to build. Here, Tanget al. report a fabrication of inhomogeneous strains with a linear gradient as giant as 106 per meter in a BiFeO3 nanostructure array grown on a LaAlO3substrate.